(3ajLhGd Sj(B++6 (3aj Ref bjGSj(B=s Visual C++6 In Record Time - (3ghdRfQ,SJjaf,s; (3GdYGeQj,NGdO,s; (3GdZfjej,CTQa,s ((3GdbGgQI,eUQ (B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY,s, 1999)
Offers clear,practical coverage of the Visual C++ enviroment,instruction in the principles of Windows programming,and tested,easy to follow tutorials that let you learn the language,s essential skills.
(3YfhGf LGQj (B: (3ajLhGd Sj(B++6 s
(3GdfU HGddZI GdYQHjI eJQLe ef GddZI GdGfcdjRjI(B.s
Keywords: (3GdMGSHGJ GdGdcJQhfjIs